2021
DOI: 10.3390/foods10092070
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Closures on the Flavor Composition of Wines during Bottle Aging

Abstract: Wine flavor undergoes major changes during bottle aging and can be influenced by the type of closure. The interaction between wine, the type of closure and the external environment has the potential to significantly influence the overall quality of bottled wines, especially when the storage period is relatively long (more than five years). Therefore, the choice of closure (cork, synthetic or screw cap) deserves special attention in order to establish the ideal sealing conditions for optimizing wine flavor attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…Bottle closures can affect the aroma composition of wines during aging by three main factors: (1) the oxygen ingress through the bottle which can lead to wine oxidation and the development of oxidized aromas; (2) the desorption of volatile compounds from closures into wine which can lead to pleasant (e.g., terpenes) or unpleasant (e.g., pyrazines) aromas; and (3) the scalping of volatile compounds present in wine by closures [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottle closures can affect the aroma composition of wines during aging by three main factors: (1) the oxygen ingress through the bottle which can lead to wine oxidation and the development of oxidized aromas; (2) the desorption of volatile compounds from closures into wine which can lead to pleasant (e.g., terpenes) or unpleasant (e.g., pyrazines) aromas; and (3) the scalping of volatile compounds present in wine by closures [9].…”
Section: Resultsmentioning
confidence: 99%
“…The impact of several winemaking processes in the aroma composition of sparkling wines has been studied, such as grape variety and maturity [4,5], production methods [6], yeast selection [7], and aging period in contact with lees [7,8]. However, it is well known that the type of bottle closure influences the aroma composition of wines during aging, as has been reported for still wines [9,10], but the aroma comparison between sparkling wines bottled with different types of closures has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The wine’s flavour undergoes changes during bottle ageing, which can be induced by the type of closure (cork, synthetic, or screw cap). These changes are more noticeable when the storage period is longer than the five years described by Guedes de Pinho and co-workers [ 12 ]. The permeation, sorption (scalping), or desorption phenomena among closures and wines were studied and concluded that corks helped to keep the aroma, as cork material had a low sorption capacity for some compounds, specifically non-polar ones, which were known to be directly correlated with fruity wine scents.…”
Section: Introductionmentioning
confidence: 86%
“…Ultimately, such research would be crucial to obtaining a predictive tool to improve wine production and quality [ 9 ]. Several reviews have already focused on the wine’s evolution and the main characteristics of cork [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, none of them showed the correlation that may exist between the wine ageing under a natural cork stopper and the compounds that can be extracted from cork.…”
Section: Introductionmentioning
confidence: 99%
“…During bottle ageing, the polyphenolic and volatile profiles of Port wine undergo important transformations having an impact in the commercial value of aged Vintage Port wine. Thus, the storage conditions, namely temperature and oxygen (O 2 ) exposure, are critical for color and aroma characteristics of these wines as they directly influence oxidative transformations during wine ageing [ 2 , 3 ]. Indeed, some studies have investigated the influence of dissolved O 2 and free SO 2 levels, pH, and time/temperature on the volatile profile of Port wine.…”
Section: Introductionmentioning
confidence: 99%